Hormetic Effects of Bioactive Compounds from Foods, Beverages, and Food Dressing: The Potential Role in Spinal Cord Injury. (2nd March 2021) - Fedullo, Anna Lucia; Ciccotti, Mario; Giannotta, Paolo; Alviti, Federica; Bernardi, Marco; Raguzzini, Anna; Toti, Elisabetta; Sciarra, Tommaso; Peluso, Ilaria
Abstract : Spinal cord injury (SCI) is a damage or trauma to the spinal cord resulting in a total or partial loss of motor and sensory function. SCI is characterized by a disequilibrium between the production of reactive oxygen species and the levels of antioxidant defences, causing oxidative stress and neuroinflammation. This review is aimed at highlighting the hormetic effects of some compounds from foods, beverages, and food dressing that are able to reduce oxidative stress in patients with SCI. Although curcumin, ginseng, and green tea have been proposed for SCI management, low levels of antioxidant vitamins have been reported in individuals with SCI. Mediterranean diet includes food rich in vitamins and antioxidants. Moreover, food dressing, including spices, herbs, and extra virgin olive oil (EVOO), contains multiple components with hormetic effects. The latter involves the activation of the nuclear factor erythroid-derived 2, consequently increasing the antioxidant enzymes and decreasing inflammation. Furthermore, EVOO improves the bioavailability of carotenoids and could be a delivery system for bioactive compounds. In conclusion, Mediterranean dressing in addition to plant foods can have an important effect on redox balance in individuals with SCI.